Rare Manifestation of a Rare Disease, Acute Liver Failure in Adult Onset Still’s Disease: Dramatic Response to Methylprednisolone Pulse Therapy—A Case Report and Review - Nalini Valluru; Venkata S. Tammana; Michael Windham; Eyasu Mekonen; Rehana Begum; Andrew Sanderson (Case Reports in Medicine)
Adult onset Still’s disease (AOSD) is a rare systemic inflammatory disorder of unknown etiology. It is characterized by daily fevers, arthralgias or arthritis, typical skin rash, and leukocytosis. Hepatic involvement is frequently observed in the course of AOSD with mildly elevated transaminases and/or hepatomegaly. Fulminant hepatic failure, occasionally requiring urgent liver transplantation, is a rare manifestation of AOSD. Here, we present a case of 22-year-old woman with no significant medical history who initially came with fever, arthralgias, myalgias, generalized weakness, and sore throat. Laboratory data showed mildly elevated transaminases and markedly elevated ferritin levels. She was diagnosed with AOSD based on Yamaguchi diagnostic criteria and was started on prednisone. Three months later, while she was on tapering dose of steroid, she presented with fever, abdominal pain, jaundice, and markedly elevated transaminases. Extensive workup excluded all potential causes of liver failure. She was diagnosed with AOSD associated acute liver failure (ALF). Intravenous (IV) methylprednisolone pulse therapy was started, with dramatic improvement in liver function. Our case demonstrated that ALF can present as a complication of AOSD and IV mega dose pulse methylprednisolone therapy can be employed as a first-line treatment in AOSD associated ALF with favorable outcome.